Estado, políticas públicas e gestão dos recursos hídricos - Nascimento, Mayara Silva (2020)
This research investigates the relationship between state actions and the process of creating public environmental policies. More specifically, it is dedicated to the study of the elements that combined in the National Water Resources Policy construction and, from a comparative perspective, Sergipe State Water Resources Policy through their similarities and distinctions. From the this empirical object framing, we turn to the promotion of an analysis regarding the water institutionalization management processes in the country, as well as its instrumentalization through the launch of various political, administrative, economic, technical and social tools. For this, the set of questions that develop the analysis revolves around three approaches: the role of the State in the processes that give rise to public policies; resource drive strategies to mold its shape; the importance of participatory management for the state decentralization through river basin committees’ creation. In this context, a theoretical model that comprises the public policies construction from the process dimension was launched, as an intricate set of interactions that develop over a given period, encompassing a plurality of actors, from those allocated in the State sphere even those in the societal sphere. However, the decision weight would be on the holders of the highest technical expertise degree. On the other hand, we mobilize the “State in action” thesis and how its organizational and institutional capacity produces political practices that result in different public policies models. The paths to reach such pretensions were followed through methodological resources based on documentary analysis, mainly of the law project 2249-1991, as well as semi-structured interviews with technicians and state officials. This research conclusions point out that the proposal processing resulted in the three principles that would determine the new Brazilian State management format: integration, participation and decentralization. However, reforms in water resources management mechanisms in Brazil since the 1980s, while contributing to the incorporation of new institutions and actors into decision-making arenas, have retained heretofore structures. The point was that the new political behaviors were gradually making the old ones unfeasible or merging, resulting in completely new political practices. Approaching the local context, the Public Administration practices in Sergipe, referring to the demands linked to the elaboration of such policy, were conducted and schematized in State-specific decision-making structures. Finally, the watershed-based management model administered by the watershed committees is an important tool to reverse this scenario, as their functioning demonstrates a still embryonic decentralization process, even for a two-decade-old policy.